Pengaruh Metode Preview, Question, Read, Reflect, Recite, Review (PQ4R) Terhadap Hasil Belajar Bahasa Indonesia Siswa Kelas IV SD Negeri Lariang Bangi 1 Kota Makassar - Syamsiah Syamsiah; Muh. Faisal (Seminar Nasional LP2M UNM, 2017)
Abstract – All information about the formatting requirements is contained in this document. Please review it carefully. You may use the document as a template and copy/paste your paper content here – this is probably the easiest option. Several styles have been included in this template to facilitate formatting – you may find it easier to use them instead of formatting each segment differently. Note that it is important to adhere to the requirements exactly, as this will form the camera-ready version that will be used to produce the Proceedings. The limitations on the length of the document are as follows. The abstract should not exceed 200-300 words; further, the title, authors, abstract, keywords, and references are excluded from (but all text, figures, tables, and appendices are included in) the overall page counts given next. The number of page of each paper is four (4) pages. Key words: Metode PQ4R dan Hasil Belajar Bahasa Indonesia